PROBABLE ANTICONVULSIVE MECHANISMS OF REPETITIVE TRANSCRANIAL MAGNETIC STIMULATION AND PREDICTORS OF ITS EFFECTIVITY - O. V. Kisten; V. V. Evstigneev (Эпилепсия и пароксизмальные состояния, 2016)
Abstract: the data of analysis of probable anticonvulsive mechanisms of repetitive transcranial magnetic stimulation (rTMS) are presented on the article. The analysis bases on review of scientific publications and proper researches. Clinical, neurophysiological and neurovisualization predictors of complex therapy with rTMS course effectivity are interpreted what permit to prognoses the outcomes of new technology using and lead stimulation with reliable result of effectivity.